2021
DOI: 10.1002/anie.202015975
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐Mining‐Based Discovery of the Cyclic Peptide Tolypamide and TolF, a Ser/Thr Forward O‐Prenyltransferase

Abstract: Cyanobactins comprise a widespread group of peptide metabolites produced by cyanobacteria that are often diversified by post‐translational prenylation. Several enzymes have been identified in cyanobactin biosynthetic pathways that carry out chemically diverse prenylation reactions, representing a resource for the discovery of post‐translational alkylating agents. Here, genome mining was used to identify orphan cyanobactin prenyltransferases, leading to the isolation of tolypamide from the freshwater cyanobacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Purushothaman et al [61] appeared to skip the in silico precursor sequence mining process and instead used the tailoring enzyme of interest to narrow down their candidates. They were targeting a tailoring enzyme found in some cyanobactin BGCs, F-type prenyltransferases, and constructed a sequence similarity network from the entire InterPro family of around 100 cyanobactin prenyltransferases.…”
Section: Global Genome Mining For Rippsmentioning
confidence: 99%
See 1 more Smart Citation
“…Purushothaman et al [61] appeared to skip the in silico precursor sequence mining process and instead used the tailoring enzyme of interest to narrow down their candidates. They were targeting a tailoring enzyme found in some cyanobactin BGCs, F-type prenyltransferases, and constructed a sequence similarity network from the entire InterPro family of around 100 cyanobactin prenyltransferases.…”
Section: Global Genome Mining For Rippsmentioning
confidence: 99%
“…They identified the other genes within the BGC of TolF and successfully produced novel cyanobactin tolypamide, in addition to a stable TolF prenyltransferase. Characterizing TolF revealed that it differed from TruF1 in the way it prenylates in the forward direction instead of reverse, thus granting researchers mechanistic insight into Ser-and Thr-prenylating enzymes when TruF1 was unavailable for extensive study [61].…”
Section: Global Genome Mining For Rippsmentioning
confidence: 99%
“…PCC 7601 as a producer of tolypamide, a cyanobactin with antimicrobial activity structurally differentiated by bearing a prenyl moiety bound to a threonine residue (▶ Fig. 2) [35]. Another example for data mining in a new taxon is the genus Micromonospora, whose members can produce analogues of ramoplanin and enduracin.…”
Section: Achievements and Latest Research Examplesmentioning
confidence: 99%
“…The process is catalysed by heterocyclases and leads to the formation of thiazole, thiazoline, oxazole, or oxazoline [14,15]. The other common post-translational modification is the prenylation of Tyr, Ser, Thr, Trp, His, and the guanidine group in Arg, which is accomplished by different prenyltransferases [12,[16][17][18][19]. Some cyanobactins, including patellamides and ulithiacyclamide, exhibit in vitro antitumor activity [20].…”
Section: Introductionmentioning
confidence: 99%